Preserving and Advertising the Memory of Corporal Expressions in Ibirité: Knowing the routine of TeacherTraining in Rural Areas – Rosario’s Farm. - Guedes Costa e Silva, Marina; Monteiro Dias Lima, Cassia Danielle; Bicalho da Cunha, Luciana; de Melo Grifo Taveira, Fernanda; Menezes Rufino, Raiane; Marques da Silva, Tatiane (Guará Journal, 2018)
This study presents the extension project from Universidade do Estado de Minas Gerais Campus Ibirité entitled “Preserving and Advertising the Memory of Corporal Expressions in Ibirité”. The authors sought to locate and catalog documents related to the theme, which are under Helena Antipoff Memorial protection. Initially our time was dedicated to cataloguing the journals produced by subjects from the Teacher’s Training School, Improvement Courses and the Instituto Superior de Educação Rural (ISER), from 1950 to 1960. We created a Catalogue Card for each journal which is an instrument used to obtain and register information about the document. The analysis of the journals enabled the understanding of the body education in Ibirité. As a result we obtained a Thematic Catalog of References elaboration; an Exhibition organization; the production of monographies and besides that, graduating professors who recognize the importance of the dialogue between the University and the community surrounding it.